The impact of physical maltreatment history on the adolescent mother-infant relationship: mediating and moderating effects during the transition to early parenthood. - Milan, Stephanie; Lewis, Jessica; Ethier, Kathleen; Kershaw, Trace; Ickovics, Jeannette R (Journal of abnormal child psychology, 2004)
Using attachment theory as a framework, this paper examines how pregnant adolescents' experiences of physical maltreatment during childhood influence the subsequent mother-infant relationship in 203 low-income adolescents followed from the 3rd trimester of pregnancy through the 1st year of parenthood. The relation between physical maltreatment history and early difficulty in the mother-infant relationship was mediated by adolescents' evaluations of the relationship with their primary caretaker and the feelings they associated with motherhood measured prior to childbirth. In addition, a supportive romantic relationship during pregnancy acted as a protective factor by moderating the impact of maltreatment history on the quality of the subsequent mother-infant relationship. Findings support the importance of assessments and interventions that consider the social context and relational history of pregnant and parenting adolescents.
Keywords: Adolescent; Child; Child Abuse; Female; Humans; Maternal Age; Mother-Child Relations; Object Attachment; Parenting; Pregnancy; Pregnancy in Adolescence; Questionnaires; Social Support